Mediating factors in the relationship between smartphone addiction and sleep quality: depression, stress, and anxiety - Elkin, Nurten; Kutuk, Hasan; Soydan, Ayse Mucella; Tanriver, Sultan Cakmak (ASSOC MEDICA BRASILEIRA, 2025)
OBJECTIVE: The aim of the study was to examine the mediating role of depression, stress, and anxiety in the relationship between smartphone addiction and sleep quality. METHODS: Data were collected from 514 university students using validated self-report measures. Correlation and mediation analyses were performed to examine the relationships between variables. FINDINGS: Smartphone addiction is negatively associated with sleep quality and positively related to depression, stress, and anxiety. Depression, stress, and anxiety are negatively correlated with sleep quality. The analysis revealed that these three factors partially mediate the relationship between smartphone addiction and sleep quality. CONCLUSION: The findings indicate that interventions targeting smartphone addiction could potentially alleviate its adverse effects on sleep quality, particularly by addressing underlying psychological factors such as depression, stress, and anxiety. These results obtained during the research process were discussed in relation to similar studies in the literature.
Keywords: Smartphone addiction; Depression; Stress; Anxiety; Sleep quality; General & Internal Medicine